Psychosocial factors associated with repeated hospitalisation in men with alcohol dependence: A hospital based cross sectional study - Jose, Kurian; R.J. Khess, Christoday; Uvais, N.A. (International Journal of Psychosocial Rehabilitation, 2018)
Background: Relapse and repeated hospitalisation is common in alcohol dependence syndrome, which is mediated by several biological and psychological factors. This study expired the association between demographic and clinical variables and various psychosocial factors such as family environment, social network, coping skills and perceived stress, between the repeatedly admitted patients and first time admitted patients. Methods: Structured assessments of demographic and clinical parameters, family functioning, social networks, coping skills and perceived stress were carried out among repeatedly admitted male patients with alcohol dependence (n=30) and compared with first time admitted male patients (n=30). Results: Patients who are repeatedly admitted were significantly likely to have family history of alcoholism, alcoholism among first degree relatives, past history of delirium tremens, severe alcohol intake, poor social support, poor social network, negative family environment, maladaptive coping strategies and higher perceived stress. Conclusion: Our study added further evidence in support of the importance of specific psychosocial and clinical factors in relapse and repeated hospitalisation. The study results have clinical, educational , research and policy implications